PENGARUH KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Pariwisata yang Terdaftar di Bursa Efek Indonesia periode 2017-2019) - Willy Nurhayadi; Abdurrohman Abdurrohman; Nefi Nafisah (Jurnal Akuntansi dan Pajak, 2023)
This study was conducted to determine the effect of managerial ownership and profitability on firm value using quantitative research methods. Sampling using purposive sampling techniquewith the number of research samples 55. The results of the study, concluded that managerial ownership has a significant effect on firm value. Evidenced by a significance value of 0.028 < 0.05. Profitability has a significant effect on firm value. Evidenced by a significance value of 0.038 < 0.05. Simultaneously obtained a significance value of 0.014 < 0.05. The conclusion of this study is that managerial ownership has a significant effect on firm value. Profitability has a significant effect on firm value and simultaneously managerial ownership and profitability affect firm value.